Kinetic study of mono- and disaccharides by surface plasmon resonance optical sensor / Wan Yusmawati Wan Yusoff, W. Mahmood Mat Yunus and Zainal Abidin Talib - Wan Yusoff, Wan Yusmawati; Mat Yunus, W. Mahmood; Talib, Zainal Abidin (2004)
In this study, the Kretschmatm surface plasmon resonance (SPR) technique is used to investigate the optical properties and kinetic behavior of mono- and disaccharide molecules to the gold surface. Two types of saccharides that are mono- and disaccharides (glucose, maltose and sucrose) in water at different level of concentration have been used in the angle scan SPR measurements. All measurements were carried out at room temperature with He-Ne laser (632.8nm, 5mW) was used as a light source. When the medium outside metal (gold) films is changed from air to saccharide solutions, the resonance at1gle shifted to the higher values. The shifts of resonat1ce angle (Ꝋspp) increased linearly with the saccharides concentration in which the detection limit and detection sensitivity could be quantified. The sensitivity of the detection was 4.68®/(mol/I), 7.40®/(mol/l) and 9.42®/(mol/l) for glucose, maltose and sucrose, respectively. In addition, the detection limit of this optical sensor was estimated to be better than 0.005mol/1 for those three saccharide solutions. The shift of resonance angle (t-.8spp) increased rapidly with time for the first 200 minutes before it reached a constant value. It is noticed that the disaccharide molecules give response 30% better than monosaccharide molecules.